MENGGAGAS HUKUM ISLAM YANG AKOMODATIF-TRANSFORMATIF DALAM KONTEKS LEGAL PLURALISM DI INDONESIA - Syafi'i, Ahmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2019)
Islamic law represents a whole of things. In the early times, Islamic law is a product of divine revelation, prophetic tradition, and custom. In this respect, Islamic law is not only as God's provision which deny human interest, but also human need to regulate society which undergo the on going process. Therefore, costums and traditions were the organic elements, which shape unity of law. Local knowledge and universal values fundamentally enriched Islamic law. This argument is debatable on account of how what some extent customs and traditions can influence or shape the Islamic law. Indonesia is not an exeption. Talking about Islamic law's position in the context of the Indonesian Legal Pluralism was not easy because it has something to do with the structure of Indonesian socio-cultural and socio political reality. This, in turn, needs the special policy through thought and political action.